Intractable sacroiliac joint pain treated with peripheral nerve field stimulation - Shushovan Chakrabortty; Sanjeev Kumar; Deepak Gupta; Sruthi Rudraraju (Wolters Kluwer Medknow Publications, 2016)
As many as 62% low back pain patients can have sacroiliac joint (SIJ) pain. There is limited (to poor) evidence in regards to long-term pain relief with therapeutic intra-articular injections and/or conventional (heat or pulsed) radiofrequency ablations (RFAs) for SIJ pain. We report our pain-clinic experience with peripheral nerve field stimulation (PNFS) for two patients of intractable SIJ pain. They had reported absence of long-term pain relief (pain relief >50% for at least 2 weeks postinjection and at least 3 months post-RFA) with SIJ injections and SIJ RFAs. Two parallel permanent 8-contact subcutaneous stimulating leads were implanted under the skin overlying their painful SIJ. Adequate stimulation in the entire painful area was confirmed. For implantable pulse generator placement, a separate subcutaneous pocket was made in the upper buttock below the iliac crest level ipsilaterally. During the pain-clinic follow-up period, the patients had reduced their pain medications requirements by half with an additional report of more than 50% improvement in their functional status. The first patient passed away 2 years after the PNFS procedure due to medical causes unrelated to his chronic pain. The second patient has been comfortable with PNFS-induced analgesic regimen during her pain-clinic follow-up during last 5 years. In summary, PNFS can be an effective last resort option for SIJ pain wherein conventional interventional pain techniques have failed, and analgesic medication requirements are escalating or causing unwarranted side-effects.